Characterization of Malignant Melanoma Using Vibrational Spectroscopy - Ziad Hammody; Ranjit Kumar Sahu; Shaul Mordechai; Emanuela Cagnano; Shmuel Argov (The Scientific World Journal)
Malignant melanoma, a malignant neoplasm of epidermal melanocytes is the third most common skin cancer. In many cases, melanoma develops from nevus, which is considered as the nonmalignant stage. Fourier transform infrared microspectroscopy (FTIR-MSP), which is based on characteristic molecular vibrational spectra of cells, was used to investigate spectral differences between melanoma, nevus, and the corresponding normal epidermis. In the present work, FTIR-MSP was performed on formalin-fixed biopsies of melanoma and nevi along with the adjoining histologically normal epidermis to understand the biochemical variations from the epidermis and identify suitable parameters for differentiation of nevi from melanoma. The comparative analysis of various parameters calculated from the spectral data of the normal epidermis and the abnormal regions showed that the changes in the nucleic acids was a significant indicator of the abnormal nature of the tissues. The RNA/DNA ratio was decreased in case of both melanoma and nevus compared to the epidermis. The amide II/amide I ratio was greater for nevus and melanoma compared to the epidermis. In contrast to other organs, the analysis of carbohydrates was not found as a suitable indicator in case of malignant melanoma. Shifts in band wave number were found to be a major distinguishing feature between the melanoma and compound nevi. The present study helps in the identification of spectral features suitable for distinction of melanoma from nevus that appear similar even in FTIR spectral features and thus can pave the way for development of in vivo screening systems based on these diagnostic markers.